Buying green and social from abroad: Are biomassfocused voluntary sustainability standards useful for European public procurement? - Tina Beuchelt (University of Bonn, Center for Development Research (ZEF), 2017)
European public procurement is becoming more sustainable. However, for goods with global supply chains, sustainable procurement faces several challenges. This paper highlights the sustainability challenges for biomass-based products, discusses the suitability of biomass-focused voluntary sustainability standards (VSS) to address them, and identifies experiences and knowledge gaps in the use of VSS in European public procurement. The paper is based on a comprehensive literature review and a case study. Biomass-based products can have major negative environmental and social impacts in their global supply chains. Biomass-focused VSS using third-party certification, contribute to avoiding such hazards. VSS are used by public procurers to (i) establish sustainability criteria for tender offers, (ii) minimize risks, and (iii) verify compliance with their criteria. Large knowledge gaps exist with respect to increasing sustainability of procurement. The impact of sustainably procured goods as well as of more recently created biomass-based VSS is uncertain. The strictness level of VSS necessary to deliver the desired sustainability effects is not clear. Large data gaps exist, e.g., how frequently which type of VSS is used for which products and for what reasons, and where procurers compromise between desired traits and limited market offers. This information would support a dialogue between procurers, business, and policy makers to stimulate markets towards more sustainable products.
Keywords: 330